Application of novel AI-based algorithms to biobank data: uncovering of new features and linear relationships - Sherlock, Lee; Martin, Brendan R.; Behsangar, Sinah; Mok, K. H. (Frontiers in Medicine, 2023)
We independently analyzed two large public domain datasets that contain 1H-NMR spectral data from lung cancer and sex studies. The biobanks were sourced from the Karlsruhe Metabolomics and Nutrition (KarMeN) study and Bayesian Automated Metabolite Analyzer for NMR data (BATMAN) study. Our approach of applying novel artificial intelligence (AI)-based algorithms to NMR is an attempt to globalize metabolomics and demonstrate its clinical applications. The intention of this study was to analyze the resulting spectra in the biobanks via AI application to demonstrate its clinical applications. This technique enables metabolite mapping in areas of localized enrichment as a measure of true activity while also allowing for the accurate categorization of phenotypes.